Research design and methods for studying cultures - De Munck, Victor C. (Altamira Press, 2009)
A concise methods book, Research Design and Methods for Studying Cultures emphasizes that all methods are related as parts of a research design and must be chosen with respect to the larger research objective of anthropology.